The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5530/pj.2019.11.183
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Activity of Ethanolic Extract of Macaranga Gigantea Leaf and Its Major Constituent

Abstract: Introduction: This research main goal is to study the antiplasmodial activity of Macaranga gigantea leaf ethanolic extract and its major components on malaria parasites using ex vivo model. Methods: This study was conducted by extraction of M. gigantea leaves using ethanol and isolation of its major constituent. The extract and isolate were tested ex vivo on Balb-C mice's blood after i.p. administration of Plasmodium berghei strain ANKA. Antiplasmodial activity was observed from mice blood treated by various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Amiri and collaborators [ 42 ] also demonstrated that apigenin significantly suppressed P. berghei parasiteamia by 69.74, 50.3, and 49.23% at concentrations of 70, 35 and 15 mg/kg/day, respectively in a murine malaria model. Muhaimin and collaborators [ 43 ] identified apigenin as major constituent in the ethanolic extract of Macaranga gigantea (Rchb. f. & Zoll.)…”
Section: Discussionmentioning
confidence: 99%
“…Amiri and collaborators [ 42 ] also demonstrated that apigenin significantly suppressed P. berghei parasiteamia by 69.74, 50.3, and 49.23% at concentrations of 70, 35 and 15 mg/kg/day, respectively in a murine malaria model. Muhaimin and collaborators [ 43 ] identified apigenin as major constituent in the ethanolic extract of Macaranga gigantea (Rchb. f. & Zoll.)…”
Section: Discussionmentioning
confidence: 99%
“…Several secondary metabolites from plants such as alkaloids, flavonoids, and triterpenoids have been reported to have antimalarial activity [31][32][33]. Terpenoids have an important role as antimalarial agents by inhibiting the Plasmodium parasites' growth from ring forms to trophozoites, and can inhibit nutrient uptake by inhibiting the permeation pathway [34,35]. Some antimalarial terpenoids isolated from other Euphorbiaceae plants have been reported, such as betulinic acid from Uapaca nitida Müll-Arg [36]; 8, 9secokaurane diterpenes from Croton kongensis Gagnep [37]; geranylgeraniol from Croton lobatus L. [38]; poly-O-acylated jatrophane diterpenes from Pedilanthus tithymaloides (L.) Poit [39]; steenkrotin A from Croton steenkampianus Gerstner [40]; 2α-hydroxyjatropholone from Jatropha integerrima Jacq [41]; jatrophone diterpenes from Jatropha isabelli Müll.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] The plant is also known to have active phytochemicals constituents, especially on its leaves. 7,21 Solvent evaporation method has been widely and extensively used to prepare polymeric microparticles containing different drugs and in the development of modified release systems. 22,23 It is a rapid process that does not involve severe heat treatment; therefore, it is a suitable method to preserve biological products, including temperature sensitive products, without their degradation; it also allows for storage at room temperature.…”
Section: Introductionmentioning
confidence: 99%